2017
DOI: 10.1002/hep.29488
|View full text |Cite
|
Sign up to set email alerts
|

Continuous renal replacement therapy is associated with reduced serum ammonia levels and mortality in acute liver failure

Abstract: In a large cohort of ALF patients, hyperammonemia was associated with high-grade HE and worse 21-day TFS. CRRT was associated with a reduction in serum ammonia level and improvement of 21-day TFS. (Hepatology 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
139
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 27 publications
0
139
2
3
Order By: Relevance
“…A study from the US Acute Liver Failure Study Group had 61 patients on CRRT. After adjusting for other factors, CRRT use on day 1 was significantly associated with lower 21‐day poststudy, transplant‐free, all‐cause mortality (adjusted odds ratio of 0.47 [95% CI, 0.26‐0.82]) and reduced ammonia levels . In the current series, the use of CRRT and plasmapheresis was particularly low during the study period.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…A study from the US Acute Liver Failure Study Group had 61 patients on CRRT. After adjusting for other factors, CRRT use on day 1 was significantly associated with lower 21‐day poststudy, transplant‐free, all‐cause mortality (adjusted odds ratio of 0.47 [95% CI, 0.26‐0.82]) and reduced ammonia levels . In the current series, the use of CRRT and plasmapheresis was particularly low during the study period.…”
Section: Discussionmentioning
confidence: 54%
“…After adjusting for other factors, CRRT use on day 1 was significantly associated with lower 21-day poststudy, transplant-free, all-cause mortality (adjusted odds ratio of 0.47 [95% CI, 0.26-0.82]) and reduced ammonia levels. (43) In the current series, the use of CRRT and plasmapheresis was particularly low during the study period. More recently, we started using plasmapheresis and CRRT more frequently, and we have seen some beneficial effect.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The large retrospective study from the USALF study group found at as compared to CVVHF, IHD failed to lower circulating ammonia concentrations and was associated with increased mortality. 4 The use of continuous rather than intermittent forms of RRT in patients with ALF is now advised in the Clinical Practice Guidelines for ALF from the European Association for the Study of Liver Disease. 5 Andrew J.…”
mentioning
confidence: 99%
“…
We read with interest the article by Cardoso et al, (1) who reported that continuous renal replacement therapy for acute liver failure (ALF) was associated with a reduction in serum ammonia level and improved 21-day transplant-free survival in a large, multicenter study.First of all, we applaud their efforts for the diagnosis and treatment of ALF and continuous contributions targeting whole fields of ALF as the U.S. ALF Study Group, different from the Japanese one. We realize how difficult these studies are to perform in infrequent and life-threatening diseases like ALF.We also believe an artificial liver support system sustaining patients in good condition, including restoration of consciousness until recovery of the native liver or performance of liver transplantation, is essential for the improvement of the poor prognosis of ALF, although it does not induce liver regeneration.
…”
mentioning
confidence: 99%